Tindak Tutur Direktif Dan Ekspresif Surat Kabar HarianKompas Kolom Surat Kepada Redaksi Edisi Februari-Maret 2016 Dan Implementasinya Pada Pembelajaran Bahasa - Widodo, Slamet; , Drs. Andi Haris Prabawa, M.Hum (2016)
Language in daily life are used to communicate. Communication occurs between the speakers and speakers colleague. Speakers and speakers colleague who communicate with each other would produce a narrative. One of the speech that became a study in this research is the directive and expressive speech acts. The purpose of this research are 1) to describe a form of directive and expressive speech acts in the column Surat Kepada Redaksi of the Kompas daily newspaper February to March 2016 edition. 2 ) to explain the implementation of the directive and expressive speech acts that teachers doing at teaching and learning in SMPN 2 Kalijambe. The method that used in this research is descriptive qualitative. The data resource in this reserach is the column Surat Kepada Redaksi of the Kompas daily newspaper February to March 2016 edition. The data in this research is a form of directive and expressive speech acts at Kompas daily newspaper column Surat Kepada Redaksi February to March 2016 edition and the implementation that teachers doing in teaching and learning in SMPN 2 Kalijambe. Data collection technique in this research used reseptive methods. This method has basic technique that is tapping techniques. Data analysis that used in this research is equal methods. This research produce are 1) directive speech acts form based on 20 data lingual marker and directive speech acts based on 14 data non lingual marker and than expressive speech acts form based on 15 data lingual marker and expressive speech acts based on 11 data non lingual marker. 2) implementation of the research results that related to learning at Junior High School (JHS), which is exist in the syllabus 2013 Curriculum with the core competence are 4. Trying , 4.4 Summarizing result observation text, descriptive feedback, exposition, explanation, and short stories either verbally or writing. Specifically refers to arrange descriptive responses text . Keywords: speech act, directive and expressive speech acts, learning.